PROCEDURAL REQUIREMENTS FOR THE APPLICATION OF THE DENIAL OF BENEFITS CLAUSE IN INVESTMENT ARBITRATION: WHY IS IT HARD TO SAY NO? - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
International treaties for the protection and encouragement of foreign investments represent kind of a bargain by which a host State of the investment agrees to provide the investor of the other contracting party with particular substantive-law protection, motivated by a desire to attract foreign capital. However, the corporate structure of the investment could be organized in a way that allows natural or legal persons to whom this kind of protection is not offered to “hide” behind the investment. Denial of Benefits Clause is an instrument that is intended to enable the host State to deny the protection offered by a Treaty to such investments. The paper discusses the application of the Denial of Benefits Clause by arbitral tribunals, with particular emphasis on procedural requirements which so far proved to be a significant obstacle for the efficient use of the clause in investment disputes.